Optimization of the incubation time and temperature for spermatozoa extraction in freshwater crayfish Pontastacus leptodactylus (Eschscholtz, 1823) - Farhadi, Ardavan; Harlioglu, Muzaffer Mustafa; Gur, Seyfettin; Acisu, Tutku Can (Elsevier Science Bv, 2018)
Determination and control of spermatozoa quality in crustacean aquaculture is an important issue for successful and controlled reproduction. Investigation of spermatozoa number in spermatophores is a basic and common parameter for determining the reproductive quality in farmed decapods. In the present study, spermatozoa extraction from spermatophores located in the ductus deferens was conducted in Pontastacus leptodactylus using different incubation times and temperatures. The results indicate that the duration of incubation and temperature affected (P < 0.05) spermatozoa extraction. Greater temperatures (40 and 75 degrees C) resulted in a reduction (P < 0.05) in number of extracted spermatozoa. In contrast, more spermatozoa were extracted when the 4 and 23 degrees C temperatures were imposed. After 4 h of incubation, the number of extracted spermatozoa were greatest in number at 23 degrees C. In conclusion, the greater numbers of crayfish spermatozoa can be obtained when the ductus deferens containing spermatophores is incubated at 23 degrees C for 4 h as compared with other temperatures and incubation durations. The results of present study are useful for assessing spermatozoa quality in aquaculture as well as the extraction of spermatozoa for research purposes.
Keywords: Spermatophore; Decapod; Reproduction; Spermatozoa count; Spermatozoa quality